Breathing in Manhattan: Carola Speads - The German Jewish Gymnastics Instructor Who Brought Mindfulness to America - Ribbat, Christoph

Experimental studies of the excitonic nonlinear response of GaAs-based type-I and type-II quantum well structures interacting with optical and terahertz fields - Meier, Torsten; Stein, M.; Schäfer, F.; Anders, D.; Littmann, J. H.; Fey, M.; Trautmann, Alexander; Ngo, C.; Steiner, J. T.; Reichelt, Matthias; Fuchs, C.; Volz, K.; et al. (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of quantum well excitons is investigated experimentally using polarization resolved four wave mixing, optical-pump optical-probe, and optical-pump Terahertz-probe spectroscopy. The four-wave mixing data reveal clear signatures of coherent biexcitons which concur with straight-forward polarization selection rules at the Γ point. The type-I samples show the well-established time-domain beating signatures in the transients as well as the corresponding spectral signatures clearly. The latter are also present in type-II samples; however, the smaller exciton and biexciton binding energies in these structures infer longer beating times which, in turn, are accompanied by faster dephasing of the type-II exciton coherences. Furthermore, the THz absorption following spectrally narrow, picosecond excitation at energies in the vicinity of the 1s exciton resonance are discussed. Here, the optical signatures yield the well-established redshifts and blueshifts for the appropriate polarization geometries in type-I quantum well samples also termed “AC Stark Effect”. The THz probe reveals intriguing spectral features which can be ascribed to coherent negative absorption following an excitation into a virtual state for an excitation below the 1s exciton resonance. Furthermore, the scattering and ionization of excitons is discussed for several excitation geometries yielding control rules for elastic and inelastic quasiparticle collisions.

Terahertz-induced anomalous currents following the optical excitation of excitons in semiconductor quantum wells - Meier, Torsten; Ngo, C.; Priyadarshi, S.; Duc, H. T.; Bieler, M. (Ultrafast Phenomena and Nanophotonics XXVII)
Anomalous currents refer to electronic currents that flow perpendicularly to the direction of the accelerating electric field. Such anomalous currents can be generated when Terahertz fields are applied after an optical interband excitation of GaAs quantum wells. The underlying processes are investigated by numerical solutions of the semiconductor Bloch equations in the length gauge. Excitonic effects are included by treating the manybody Coulomb interaction in time-dependent Hartree-Fock approximation and additionally also carrier-phonon scattering processes are considered. The band structure and matrix elements are obtained from a 14-band k · p model within the envelope function approximation. The random phase factors of the matrix elements that appear due to the separate numerical diagonalization at each k-point are treated by applying a smooth gauge transformation. We present the macroscopic Berry curvature and anomalous current transients with and without excitonic effects. It is demonstrated that the resonant optical excitation of excitonic resonances can significantly enhance the Berry curvature and the anomalous currents.

Analysis of the nonlinear optical response of excitons in type-I and type-II quantum wells including many-body correlations - Meier, Torsten; Trautmann, Alexander; Stein, M.; Schäfer, F.; Anders, D.; Ngo, C.; Steiner, J. T.; Reichelt, Matthias; Chatterjee, S. (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of quantum well excitons excited by optical fields is analyzed by numerical solutions of the semiconductor Bloch equations. Differential absorption spectra are computed for resonant pumping at the exciton resonance and the dependence of the absorption changes on the polarization directions of the pump and probe pulses is investigated. Coherent biexcitonic many-body correlations are included in our approach up to third-order in the optical fields. Results are presented for spatially-direct type-I and spatiallyindirect type-II quantum well systems. Due to the spatial inhomogeneity, in type-II structures a finite coupling between excitons of opposite spins exists already on the Hartree-Fock level and contributes to the absorption changes for the case of opposite circularly polarized pump and probe pulses.

Gain recovery dynamics in active type-II semiconductor heterostructures - Meier, Torsten; Schäfer, F.; Stein, M.; Lorenz, J.; Dobener, F.; Ngo, C.; Steiner, J. T.; Fuchs, C.; Stolz, W.; Volz, K.; Hader, J.; Moloney, J.V.; et al. (Applied Physics Letters)

Temporal sorting of optical multi-wave-mixing processes in semiconductor quantum dots - Meier, Torsten; Grisard, S.; Trifonov, A.V.; Rose, Hendrik; Reichhardt, R.; Reichelt, Matthias; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M.; Akimov, I.A (arxiv:2302.02480)

Entanglement of particles versus entanglement of fields: Independent quantum resources - Sperling, Jan; Agudelo, Elizabeth (Physical Review A)

Detector entanglement: Quasidistributions for Bell-state measurements - Sperling, Jan; Gianani, Ilaria; Barbieri, Marco; Agudelo, Elizabeth (Physical Review A)

Tracking Quantum Coherence in Polariton Condensates with Time-Resolved Tomography - Lüders, Carolin; Pukrop, Matthias; Barkhausen, Franziska; Rozas, Elena; Schneider, Christian; Höfling, Sven; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (Physical Review Letters)
Keywords: General Physics and Astronomy

Who benefits from quality competition in health care? A theory and a laboratory experiment on the relevance of patient characteristics - Brosig-Koch, Jeannette; Hehenkamp, Burkhard; Kokot, Johanna (Health Economics)
We study how competition between physicians affects the provision of medical care. In our theoretical model, physicians are faced with a heterogeneous patient population, in which patients systematically vary with regard to both their responsiveness to the provided quality of care and their state of health. We test the behavioral predictions derived from this model in a controlled laboratory experiment. In line with the model, we observe that competition significantly improves patient benefits as long as patients are able to respond to the quality provided. For those patients, who are not able to choose a physician, competition even decreases the patient benefit compared to a situation without competition. This decrease is in contrast to our theoretical prediction implying no change in benefits for passive patients. Deviations from patient-optimal treatment are highest for passive patients in need of a low quantity of medical services. With repetition, both, the positive effects of competition for active patients as well as the negative effects of competition for passive patients become more pronounced. Our results imply that competition can not only improve but also worsen patient outcome and that patients’ responsiveness to quality is decisive.
Keywords: physician competition; patient characteristics; heterogeneity in quality responses; fee-for-service; laboratory experiment

Price Regulation, Quality Competition and Location Choice with Costly Relocation - Hehenkamp, Burkhard; Kaarbøe, Oddvar M.
We consider a model where for-profit providers compete in quality in a price-regulated market that has been opened to competition, and where the incumbent is located at the center of the market, facing high costs of relocation. The model is relevant in markets such as public health care, education and schooling, or postal services. We find that, when the regulated price is low or intermediate, the entrant strategically locates towards the corner of the market to keep the incumbent at the low monopoly quality level. For a high price, the entrant locates at the corner of the market and both providers implement higher quality compared to a monopoly. In any case, the entrant implements higher quality than the incumbent provider. Social welfare is always higher in a duopoly if the cost of quality is low. For higher cost levels welfare is non-monotonic in the price and it can be optimal to the regulator not to use its entire budget. Therefore, the welfare effect of entry depends on the price and the size of the entry cost, and the regulator should condition the decision to allow entry on an assessment of the entry cost.
Keywords: Quality competition; Price regulation; Location choice; Product differentiation

A multi-mode super-fano mechanism for enhanced third harmonic generation in silicon metasurfaces - Hähnel, David; Golla, Christian; Albert, Maximilian; Zentgraf, Thomas; Myroshnychenko, Viktor; Förstner, Jens; Meier, Cedrik (Light: Science & Applications)
We present strong enhancement of third harmonic generation in an amorphous silicon metasurface consisting of elliptical nano resonators. We show that this enhancement originates from a new type of multi-mode Fano mechanism. These ‘Super-Fano’ resonances are investigated numerically in great detail using full-wave simulations. The theoretically predicted behavior of the metasurface is experimentally verified by linear and nonlinear transmission spectroscopy. Moreover, quantitative nonlinear measurements are performed, in which an absolute conversion efficiency as high as ηmax ≈ 2.8 × 10−7 a peak power intensity of 1.2 GW cm−2 is found. Compared to an unpatterned silicon film of the same thickness amplification factors of up to ~900 are demonstrated. Our results pave the way to exploiting a strong Fano-type multi-mode coupling in metasurfaces for high THG in potential applications.
Keywords: tet_topic_meta

Online load balancing on uniform machines with limited migration - Maack, Marten (Operations Research Letters)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; Management Science and Operations Research; Software

Experimental analysis of ship motion effects on the performance of an absorption column equipped with structured packings - Mamedov, Tural; Schleicher, Eckhard; Schubert, Markus; Ehlert, Thomas; Kenig, Eugeny Y.; Hampel, Uwe

Charakterisierung des Einflusses neigungsinduzierter Strömungsformen mit dem Ansatz der hydrodynamsichen Analogie - Ehlert, Thomas; Mamedov, Tural; Schubert, Markus; Kenig, Eugeny Y.

Modellierung des Randspalts in Strukturpackungskolonnen mit dem Ansatz der hydrodynamischen Analogien - Ehlert, Thomas; Lutters, Nicole; Kenig, Eugeny Y.

"The Future of Canadian Studies: On Plowing a Lonely Furrow." - Jende, Yvonne Kristin (Zeitschrift für Kanada-Studien)

Experimentelle Kompetenz Physikstudierender. Entwicklung und erste Erprobung eines performanzorientierten Kompetenzstrukturmodells unter Nutzung qualitativer Methoden - Bauer, Anna Brigitte

Methodenentwicklung zur Simulation von hyperelastischen Klebverbindungen unter Crashbelastung - Beule, Felix; Schmelzle, Lars; Teutenberg, Dominik; Possart, Gunnar; Meschut, Gerson; Mergheim, Julia (23. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

A Formal Comparison of Advanced Digital Signature Primitives - Schürmann, Patrick

Weiterentwicklung der induktiven Schnellhärtung von Klebverbindungen für robuste Fertigungsprozesse unter Berücksichtigung von serienrelevanten Einflussfaktoren - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (23. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Morphological and mechanical properties of foamed thick-walled Wood-Plastic-Composite structures - Moritzer, Elmar; Flachmann, Felix (Journal of Cellular Plastics)
Microcellular wood fiber reinforced polymers offer the possibility to reduce the use of fossil raw materials. In particular, thick-walled structures with thicknesses greater than 6 mm offer a high potential for weight savings. This study investigates the cell structures and mechanical properties of injection-molded test specimens. The influence of different thicknesses (6–10 mm) along with different chemical blowing agents (endothermic, exothermic) with varying dosages (0–2 wt%) is analyzed. The investigations reveal that exothermic chemical blowing agents form finer cells consistently to thin-walled structures than endothermic ones. Higher foaming agent content leads to higher pore fractions, with many small cells coalescing into a large open-pore cell network. The mechanical properties depend mainly on the pore content of the sample. The specific tensile properties deteriorate with the use of chemical blowing agents (CFA), whereas the sandwich structure produced with compact edge layers has a positive influence on the specific flexural properties.
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Distribution Network Optimization: Predicting computation times to design scenario analysis for network operators - Burmeister, Sascha Christian; Schryen, Guido (Energy Systems)

Energy and Resource-efficient Forming of Gas Cylinders by Friction-Spinning - Dahms, Frederik; Homberg, Werner (Materials Research Proceedings)
Abstract. Friction-spinning as an innovative incremental forming process enables large degrees of deformation in tube and sheet metal-forming due to a self-induced heat generation in the forming zone. This paper presents new process designs for energy and resource-efficient forming of gas cylinders by friction-spinning without the use of an external heat supply. The self-generated heat enables friction-spinning process to reduce the energy demand in the manufacture of gas cylinders, which are usually manufactured with external heat (mostly fossil fuels), by 95 %. Typical gas cylinder contours, such as flattened and spherical bottom ends and cylinder necks, are manufactured by friction-spinning of AW 6060 tubular profiles with specifically designed tool path strategies. It is shown that friction-spinning enables the manufacture of typical gas cylinder contours with sufficient wall thickness and the required gas tightness without the input of external heat. Thus, this process can contribute to an increase in the energy and resource efficiency of forming processes.

Thermal conductivity of solid paraffins and several n-docosane compounds with graphite - Paul, Andreas; Baumhögger, Elmar; Dewerth, Mats-Ole; Hami Dindar, Iman; Sonnenrein, Gerrit; Vrabec, Jadran (Journal of Thermal Analysis and Calorimetry)
The technical importance of paraffins as phase change materials (PCM) in heat storage systems increases. Knowledge on the thermal conductivity of paraffins is necessary for the design and optimization of heat storage systems. However, for most paraffins solely the thermal conductivity of the liquid state has been sufficiently investigated. For the solid state, precise thermal conductivity data are only known for a few paraffins, while only generalized values are available for the remainder, some of which contradict each other. In this study, a measurement setup based on the modified guarded hot plate method is developed. It is used to investigate the thermal conductivity of several paraffines in the solid state, including pure n-docosane and its compounds with different types and concentrations of graphite. For n-docosane in the solid state, the thermal conductivity is determined to be 0.49 W/(m K). A particle size of 200 μm with a spherical shape turns out to be optimal to increase the thermal conductivity. This allows the thermal conductivity of a compound with 10% graphite to increase by a factor of three compared to the pure paraffin. Furthermore, significant differences to thermal conductivity data from the literature are found.
Keywords: Physical and Theoretical Chemistry; Condensed Matter Physics

Alterungsmechanismen von Haushaltskältegeräten - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Reineke, Michael; Kasper, Tina; Schumacher, Daniel; Vrabec, Jadran; Hüppe, Christian; Stamminger, Rainer; Hölscher, Heike; Stoll, Ragnar; Wagner, Hendrik; et al.
Die für die Berechnung des Energieeffizienzindex von Haushaltskältegeräten benötigten Parameter werden durch Norm-Messungen im Neuzustand der Geräte bestimmt. Aus früheren Untersuchungen ist bekannt, dass durch verschiedene technische Alterungsmechanismen der Energieverbrauch über eine Produktlebensdauer von 18 Jahren um bis zu 33 % zunehmen kann. Ziel des vom BMWi geförderten Projekts ALGE war es, die verschie-denen Ursachen und Einflussgrößen für die Alterung von Haushaltskältegeräten zu ermitteln und eine Alterungs-funktion zu bestimmen, die den zeitlichen Verlauf des zunehmenden Energieverbrauchs beschreibt. In diesem Projekt wurde das Alterungsverhalten von Haushaltskältegeräten durch 100 Normenergieverbrauchs-messungen an 32 real gealterten Geräten untersucht. Aus den gewonnenen Ergebnissen konnte eine Alterungs-funktion bestimmt werden, die den Anstieg des Energieverbrauchs beschreibt. Alle untersuchten Geräte wurden an der Universität Paderborn im Neuzustand vermessen und nach einer Laufzeit von bis zu 21 Jahren erneut geprüft. Bereits nach einem zweijährigen Betrieb konnte ein Mehrverbrauch von bis zu 11 % festgestellt werden. Über die durchschnittliche Produktlebensdauer von Haushaltskältegeräten von ca. 16 Jahren steigert sich der Energieverbrauch um durchschnittlich 27 %. Im Rahmen des Projekts wurden verschiedene Systemkomponenten, wie Isolierung und Verdichter, hinsichtlich ihres Alterungsverhaltens untersucht. Bei dem im Gehäuse als Isolierung verwendeten PUR-Schaum konnte über einen Zeitraum von 31 Monaten ein Anstieg der Wärmeleitfähigkeit von 19,5 W/(m⋅K) auf 24,5 W/(m⋅K) festge-stellt werden. Zur Untersuchung der Alterung der Verdichter wurden zuvor auf einem Kalorimeterteststand ver-messene Verdichter in Geräte eingebaut. Nach einem zweijährigen Betrieb wurden diese Verdichter wieder aus-gebaut und erneut vermessen. Hierbei konnte keine Änderung des COP festgestellt werden. Zusätzlich zu den technischen Parametern wurde der Einfluss des Verbraucherverhaltens analysiert. Hier zeigte sich, dass bis zu 33 % des Gesamtenergieverbrauchs nach einer mehrjährigen Nutzungsdauer verbraucherinduziert sein können.
Keywords: Haushaltskältegeräte; Energieverbrauch; Alterung; Verdichter; PUR-Schaum

Development of an adaptive coaxial concrete rheometer and rheological characterisation of fresh concrete - Josch, Sebastian; Jesinghausen, Steffen; Schmid, Hans-Joachim (Applied Rheology)
Abstract The accessibility to rheological parameters for concrete is becoming more and more relevant. This is mainly related to the constantly emerging challenges, such as not only the development of high-strength concretes is progressing very fast but also the simulation of the flow behaviour is of high importance. The main problem, however, is that the rheological characterisation of fresh concrete is not possible via commercial rheometers. The so-called concrete rheometers provide valuable relative values for comparing different concretes, but they cannot measure absolute values. Therefore, we developed an adaptive coaxial concrete rheometer (ACCR) that allows the measurement of fresh concrete with particles up to d max = 5.5 mm {d}_{{\rm{\max }}}=5.5\hspace{.5em}{\rm{mm}} . The comparison of the ACCR with a commercial rheometer showed very good agreement for selected test materials (Newtonian fluid, shear thinning fluid, suspension, and yield stress fluid), so that self-compacting concrete was subsequently measured. Since these measurements showed a very high reproducibility, the rheological properties of the fresh concrete could be determined with high accuracy. The common flow models (Bingham (B), Herschel–Bulkley, modified Bingham (MB) models) were also tested for their applicability, with the Bingham and the modified Bingham model proving to be the best suitable ones.
Keywords: Condensed Matter Physics; General Materials Science

Please Mind the Gap. Reconfiguring Solidarity through Space in Michael Nicoll Yahgulanaas' Haida Manga Art. - Jende, Yvonne Kristin (Solidarités. Réseaux – Convivialités – Confrontations/ Solidarities. Networks – Convivialities – Confrontations, 44. Annual Conference of the Association for Canadian Studies in German-Speaking Countries)

Flowability of polymer powders at elevated temperatures for additive manufacturing - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Rüther, Torben; Schmid, Hans-Joachim (Powder Technology)
Keywords: General Chemical Engineering

Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koschukow, Wikentji; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Influence of plasma coating pretreatment on the adhesion of thermoplastics to metals - Wippermann, Jan; Koshukow, Wikentij; Liebsch, Alexander; Kolbe, Björn; Meschut, Gerson; Gude, Maik (Tagungsband Münchener Leichtbauseminar 2022)

Dynamisch-mechanische Polymerpartikelverrundung zur Verbesserung der Fließfähigkeit für das selektive Lasersintern - Ponusamy, SathishKumar; Schmid, Hans-Joachim

Tax Education After WWII: How Spain, the USA, and West Germany Tried to Make Their Citizens Pay Honestly - Schönhärl, Korinna; Düll, Nasrin; Ramírez Lugo , Nadya Melina (Tax Evasion and Tax Havens since the Nineteenth Century)
State education in honest tax payment can be understood as a facet of training in citizenship, i.e. as an attempt by the modern state to standardize the behavior of its citizens and to prevent deviations. Based on this Foucauldian understanding, this exploratory article examines tax education in the United States, Spain, and West Germany from the mid-1940s to the late 1980s. During this period, the USA asserted itself as the champion of tax education and Spain consistently tried to emulate this example, albeit with more modest means and different semantic strategies from as early as the 1960s, when it was still under a autoritarian regime. The FRG, however, completely discontinued its few early attempts at tax education from the mid-1950s onwards. Even during the economic crises and tax scandals of the 1970s, there was no relaunch of the programs. The article locates the reasons for this highly uneven development in the different ideal images of the citizen in the three states.

Recapturing Old England – Nostalgia, Aristo-Anglophilia, and the Historical Roots of ITV’s ‘Downton Abbey’ - Behler, Felix (Interdisciplinary Discourses, Education and Analysis (IDEA))

Feasibility Study of Compression Molding for Large Reinforcement Structures in the Commercial Vehicle Sector - Lückenkötter, Julian; Leimbach, J.P.; Stallmeister, Tim; Marten, Thorsten; Tröster, Thomas (Materials Research Proceedings)
Abstract. Due to an increasing volume of shipments, there is a significant need for more delivery vehicles. One approach to reduce the associated increase in carbon dioxide (CO2) emissions is a new light weight design approach involving the substitution of conventional materials with glass fiber mat-reinforced thermoplastics (GMT) based on polypropylene (PP). The application of GMT by compression molding is a widely used process in the automotive industry. However, application in the commercial vehicle sector requires much larger dimensions, making it necessary to clarify whether the manufacturing process and material are suitable for semi-structural applications on this scale. To find this out, two replacement geometries are abstracted in this study and manufactured by varying the main manufacturing parameters. The feasibility can be demonstrated by recording and analyzing the resulting process variables and measuring the formed fiber distribution. At the end of the paper, recommendations are given for the production of GMT structures on the scale of commercial vehicles.
Keywords: Compression Molding; Fiber Content; Process Development; Lightweight Design

Selective Discrimination between CO and H2 with Copper–Ceria-Resistive Gas Sensors - Baier, Dominik; Priamushko, Tatiana; Weinberger, Christian; Kleitz, Freddy; Tiemann, Michael (ACS Sensors)
The production of hydrogen and the utilization of biomass for sustainable concepts of energy conversion and storage require gas sensors that discriminate between hydrogen (H2) and carbon monoxide (CO). Mesoporous copper–ceria (Cu–CeO2) materials with large specific surface areas and uniform porosity are prepared by nanocasting, and their textural properties are characterized by N2 physisorption, powder XRD, scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectroscopy. The oxidation states of copper (Cu+, Cu2+) and cerium (Ce3+, Ce4+) are investigated by XPS. The materials are used as resistive gas sensors for H2 and CO. The sensors show a stronger response to CO than to H2 and low cross-sensitivity to humidity. Copper turns out to be a necessary component; copper-free ceria materials prepared by the same method show only poor sensing performance. By measuring both gases (CO and H2) simultaneously, it is shown that this behavior can be utilized for selective sensing of CO in the presence of H2.
Keywords: Fluid Flow and Transfer Processes; Process Chemistry and Technology; Instrumentation; Bioengineering

Proof of concept for incremental sheet metal forming by means of electromagnetic and electrohydraulic high-speed forming - Holzmüller, Maik; Linnemann, Maik; Homberg, Werner; Psyk, Verena; Kräusel, Verena; Kroos, Janika (Materials Research Proceedings)
Abstract. The combination of incremental sheet metal forming and high-speed forming offers new possibilities for flexible forming processes in the production of large sheet metal components of increased complexity with relatively low forming energies. In this paper, the general feasibility and process differences between the pulse-driven high-speed forming technologies of electrohydraulic and electromagnetic forming were investigated. An example component made of EN AW 6016 aluminum sheet metal was thus formed incrementally by both processes and the forming result evaluated by an optical 3D measurement system. For this purpose, a forming strategy for electromagnetic incremental forming (EMIF) was developed, tested and adapted to the electrohydraulic incremental forming process (EHIF). The discharge energy, the tool displacement and the pressure field of the forming zone were determined as relevant parameters for the definition of an adequate tool path strategy. It was found that the EHIF process is less affected by larger distances between the tool and the blank, while this is a critical variable for force application to the component during EMIF. On the other hand, the more uniform pressure distribution of the EMIF process is advantageous for forming large steady component areas.
Keywords: Incremental Sheet Forming; Aluminium; High-Speed Forming

Investigation of Pressure Fields Generated by Two Simultaneous Discharges in Liquid Initiated by Wires - Knyazyev, Mykhaylo; Holzmüller, Maik; Homberg, Werner (Journal of Manufacturing and Materials Processing)
The pressure fields generated by two simultaneous discharges have not been investigated on any notable scale for the electrohydraulic impulse forming method. In this study, the synchronicity of two discharges is ensured by the sequential connection of two wires mounted in two spark gaps in a common volume of liquid. The objective is to experimentally confirm the equilibrium of the energies evolved in two spark gaps by means of pressure measurements. In addition, multipoint membrane pressure gauges demonstrated the feasibility of easily recording detailed pressure maps. Based on the membrane deformation mechanism and material strengthening under static and impulse conditions, the processing procedure is further developed so as to achieve better accuracy in the determination of pressure field parameters. The practical equality of the pressure fields on the left and right halves of the flat-loaded area confirms the equality of energies evolved in the two spark gaps. The direct shock waves create zones with the most intensive loading. These results provide a basis for the development of new electrohydraulic technologies involving the application of two simultaneous discharges with equal energy and pressure parameters.
Keywords: impulse; forming; electrohydraulic; discharge; wire; pressure gauge; pressure field

Studien zu Schulleistungen und ihre Aufbereitung - Neumann, Phillip (Zeitschrift für Heilpädagogik)
Keywords: Inklusion; Sonderpädagogik; Bildung; Bildungsstudien; Integration

Wässrige Glucosaminlösung als neues Lösungsmittel zur CO2-Abscheidung - Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny (Jahrestreffen der ProcessNet-Fachgruppen Fluidverfahrenstechnik und Adsoprtion)

Estimating States and Model Uncertainties Jointly by a Sparsity Promoting UKF - Götte, Ricarda-Samantha; Timmermann, Julia (12th IFAC Symposium on Nonlinear Control Systems (NOLCOS 2022))
State estimation when only a partial model of a considered system is available remains a major challenge in many engineering fields. This work proposes a joint, square-root unscented Kalman filter to estimate states and model uncertainties simultaneously by linear combinations of physics-motivated library functions. Using a sparsity promoting approach, a selection of those linear combinations is chosen and thus an interpretable model can be extracted. Results indicate a small estimation error compared to a traditional square-root unscented Kalman filter and exhibit the enhancement of physically meaningful models.
Keywords: joint estimation; unscented transform; Kalman filter; sparsity; data-driven; compressed sensing

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Methodology for Certification-Compliant Effect-Chain Modeling - Gräßler, Iris; Wiechel, Dominik; Koch, Anna-Sophie; Sturm, Tim; Markfelder, Thomas (Systems)
The success of engineering complex technical systems is determined by meeting customer requirements and institutional regulations. One example relevant to the automobile industry is the United Nations Economic Commission of Europe (UN ECE), which specifies the homologation of automobile series and requires proof of traceability. The required traceability can be achieved by modeling system artifacts and their relations in a consistent, seamless model—an effect-chain model. Currently, no in-depth methodology exists to support engineers in developing certification-compliant effect-chain models. For this purpose, a new methodology for certification-compliant effect-chain modeling was developed, which includes extensions of an existing method, suitable models, and tools to support engineers in the modeling process. For evaluation purposes, applicability is proven based on the experience of more than 300 workshops at an automotive OEM and an automotive supplier. The following case example is chosen to demonstrate applicability: the development of a window lifter that has to meet the demands of UN ECE Regulations R156 and R21. Results indicate multiple benefits in supporting engineers with the certification-compliant modeling of effect chains. Three benefits are goal-oriented modeling to reduce the necessary modeling capacity, increasing model quality by applying information quality criteria, and the potential to reduce costs through automatable effect-chain analyses for technical changes. Further, companies in the automotive and other industries will benefit from increased modeling capabilities that can be used for architecture modeling and to comply with other regulations such as ASPICE or ISO 26262.
Keywords: Information Systems and Management; Computer Networks and Communications; Modeling and Simulation; Control and Systems Engineering; Software

Characterization of Na-S Battery System Using X-ray Absorption Spectroscopy - Tonbul, Güldeniz; Kappler, Julian; Murugan, Saravanakumar; Schoch, Roland; Nowakowski, Michal; Lange, Pia; Bauer, Matthias; Buchmeiser, Michael R.

Simulation Environment for Traffic Control Systems Targeting Mixed Autonomy Traffic Scenarios - Link, Christopher; Malena, Kevin; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the 9th International Conference on Vehicle Technology and Intelligent Transport Systems)
The development of autonomous vehicles and their introduction in urban traffic offer many opportunities for traffic improvements. In this paper, an approach for a future traffic control system for mixed autonomy traffic environments is presented. Furthermore, a simulation framework based on the city of Paderborn is introduced to enable the development and examination of such a system. This encompasses multiple elements including the road network itself, traffic lights, sensors as well as methods to analyse the topology of the network. Furthermore, a procedure for traffic demand generation and routing is presented based on statistical data of the city and traffic data obtained by measurements. The resulting model can receive and apply the generated control inputs and in turn generates simulated sensor data for the control system based on the current system state.
Keywords: Traffic Simulation; Traffic Control; Car2X; Mixed Autonomy; Autonomous Vehicles; SUMO; Sensor Simulation; Traffic Demand Generation; Routing; Traffic Lights; Graph Analysis; Traffic Observer

Business Models for Cultural Event Platforms – A Taxonomy Approach - Althaus, Maike; Müller, Michelle; Vorbohle, Christian; Kundisch, Dennis (Proceedings of the International Conference on Challenges in Managing Smart Products and Services (CHIMSPAS 2023))

May I have your Attention, please? – The Interaction between Attention Screening and Reputation on Crowdworking Platforms - Laux, Florian; Poniatowski, Martin; Kundisch, Dennis (Proceedings of the 31st European Conference on Information Systems (ECIS))

Particles as Seeds for Instabilities in Uniaxially Elongated Polymer Suspension Filaments (Presentation) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Haushaltswissenschaft – Eine Diskussionsgrundlage - Küster, Christine; Klünder, Nina; Wagenknecht, Inga (Hauswirtschaft und Wissenschaft)

Musiklandschaften zwischen Rhein und Weser – Einführung - Meine, Sabine; Otto, Arnold; Süßmann, Johannes (Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert)

The Complexity of Translationally Invariant Problems beyond Ground State Energies - Gharibian, Sevag; Watson, James; Bausch, Johannes (Proceedings of the 40th International Symposium on Theoretical Aspects of Computer Science (STACS))

Critically 3-frustrated signed graphs - Cappello, Chiara; Naserasr, Reza; Steffen, Eckhard; Wang, Zhouningxin (arXiv:2304.10243)
Extending the notion of maxcut, the study of the frustration index of signed graphs is one of the basic questions in the theory of signed graphs. Recently two of the authors initiated the study of critically frustrated signed graphs. That is a signed graph whose frustration index decreases with the removal of any edge. The main focus of this study is on critical signed graphs which are not edge-disjoint unions of critically frustrated signed graphs (namely non-decomposable signed graphs) and which are not built from other critically frustrated signed graphs by subdivision. We conjecture that for any given k there are only finitely many critically k-frustrated signed graphs of this kind. Providing support for this conjecture we show that there are only two of such critically 3-frustrated signed graphs where there is no pair of edge-disjoint negative cycles. Similarly, we show that there are exactly ten critically 3-frustrated signed planar graphs that are neither decomposable nor subdivisions of other critically frustrated signed graphs. We present a method for building non-decomposable critically frustrated signed graphs based on two given such signed graphs. We also show that the condition of being non-decomposable is necessary for our conjecture.

Large-Scale Formation of DNA Origami Lattices on Silicon - Tapio, Kosti; Kielar, Charlotte; Parikka, Johannes M.; Keller, Adrian; Järvinen, Heini; Fahmy, Karim; Toppari, J. Jussi (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Nanoparticle‐Based Formulations of Glycopeptide Antibiotics: A Means for Overcoming Vancomycin Resistance in Bacterial Pathogens? - Pothineni, Bhanu Kiran; Keller, Adrian (Advanced NanoBiomed Research)
Keywords: General Medicine

Effect of Ionic Strength on the Thermal Stability of DNA Origami Nanostructures - Hanke, Marcel; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Stability of DNA Origami Nanostructures in Physiological Media: The Role of Molecular Interactions - Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Entwicklung einer Methode zur Integration der Additiven Fertigung in die Serienproduktion am Beispiel des Lasersinterns - Kruse, Anne

Detecting Novelties with Empty Classes - Uhlemeyer, Svenja; Lienen, Julian; Hüllermeier, Eyke; Gottschalk, Hanno (arXiv:2305.00983)
For open world applications, deep neural networks (DNNs) need to be aware of previously unseen data and adaptable to evolving environments. Furthermore, it is desirable to detect and learn novel classes which are not included in the DNNs underlying set of semantic classes in an unsupervised fashion. The method proposed in this article builds upon anomaly detection to retrieve out-of-distribution (OoD) data as candidates for new classes. We thereafter extend the DNN by $k$ empty classes and fine-tune it on the OoD data samples. To this end, we introduce two loss functions, which 1) entice the DNN to assign OoD samples to the empty classes and 2) to minimize the inner-class feature distances between them. Thus, instead of ground truth which contains labels for the different novel classes, the DNN obtains a single OoD label together with a distance matrix, which is computed in advance. We perform several experiments for image classification and semantic segmentation, which demonstrate that a DNN can extend its own semantic space by multiple classes without having access to ground truth.

Aspects of a Sustainability Focused Comparison of the Wire Arc Additive Manufacturing (WAAM) and the Laser Powder Bed Fusion (LPBF) Process - Wurst, Johanna; Steinhoff, Timon; Mozgova, Iryna; Hassel, Thomas; Lachmayer, Roland

Concept and Implementation of a Student Design Project for the Development of Sustainable Products - Wurst, Johanna; Rosemann, Daniel; Mozgova, Iryna; Lachmayer, Roland

Structure–Reactivity Relationships in Borane-Based FLP-Catalyzed Hydrogenations, Dehydrogenations, and Cycloisomerizations - Paradies, Jan (Accounts of Chemical Research)
Keywords: General Medicine; General Chemistry

Wirtschaft neu ausrichten. Care-Initiativen in Deutschland, Österreich und der Schweiz.

Exergaming in older adults: the effects of game characteristics on brain activity and physical activity - Müller, Helen; Baumeister, Jochen; Bardal, Ellen Marie; Vereijken, Beatrix; Skjæret-Maroni, Nina (Frontiers in Aging Neuroscience)
Introduction Exergames are increasingly used in rehabilitation settings for older adults to train physical and cognitive abilities. To meet the potential that exergames hold, they need to be adapted to the individual abilities of the player and their training objectives. Therefore, it is important to know whether and how game characteristics affect their playing. The aim of this study is to investigate the effect of two different kinds of exergame (step game and balance game) played at two difficulty levels on brain activity and physical activity. Methods Twenty-eight older independently living adults played two different exergames at two difficulty levels each. In addition, the same movements as during gaming (leaning sideways with feet in place and stepping sideways) were performed as reference movements. Brain activity was recorded using a 64-channel EEG system to assess brain activity, while physical activity was recorded using an accelerometer at the lower back and a heart rate sensor. Source-space analysis was applied to analyze the power spectral density in theta (4 Hz–7 Hz) and alpha-2 (10 Hz–12 Hz) frequency bands. Vector magnitude was applied to the acceleration data. Results Friedman ANOVA revealed significantly higher theta power for the exergaming conditions compared to the reference movement for both games. Alpha-2 power showed a more diverse pattern which might be attributed to task-specific conditions. Acceleration decreased significantly from the reference movement to the easy condition to the hard condition for both games. Discussion The results indicate that exergaming increases frontal theta activity irrespective of type of game or difficulty level, while physical activity decreases with increasing difficulty level. Heart rate was found to be an inappropriate measure in this population older adults. These findings contribute to understanding of how game characteristics affect physical and cognitive activity and consequently need to be taken into account when choosing appropriate games and game settings for exergame interventions.
Keywords: Cognitive Neuroscience; Aging

Learning Computational Thinking in Secondary School (Year 8) in Germany in International Comparison: Results from ICILS 2018 - Labusch, Amelie; Eickelmann, Birgit (Teaching coding in K-12 schools: Research and application)

Die inhaltliche Ausgestaltung schulischer Medienkonzepte als Gelingensbedingung digitalisierungsbezogener Schulentwicklungsprozesse - Schulze, Johanna; Drossel, Kerstin; Eickelmann, Birgit (Professionalisierung für digitale Bildung im Grundschulalter - Ergebnisse des Forschungsprojekts P3DiG)

Abschlussbericht zum Forschungsprojekt ‚Gelingensbedingungen und Transfer von erfolgreichen Digitalisierungsprozessen an Schulen in Nordrhein-Westfalen (GuTe DigiSchulen NRW) - Gerick, J.; Eickelmann, Birgit; Panten, B.; Rothärmel, A.; Rau, M.; Gottschalk, T.

Digitalisierungsbezogene Schulentwicklungsprozesse erfolgreich gestalten. Handreichung für die schulische Arbeit zu den Ergebnissen des Forschungsprojekts GuTe DigiSchulen NRW. - Gerick, J.; Eickelmann, Birgit; Rau, M.; Panten, B.; Rothärmel, A.; Gottschalk, T.

Optimization of inductive fast-curing of epoxy adhesive by model-based kinetics - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (International Journal of Adhesion and Adhesives)

Simulation des „viscous fingering“ Effektes in Klebverbindungen - Salten, Alexander Heinrich Johannes; Al Trjman, Mohamad; Meschut, Gerson; Kenig, Eugeny Y.

Methodenentwicklung zur Simulation des Viscous Fingering in Klebverbindungen von stahlintensiven Mischbaustrukturen - Al Trjman, Mohamad; Meschut, Gerson; Salten, Alexander Heinrich Johannes; Kenig, Eugeny Y.

Model-based condition monitoring of piezoelectric bending actuators - Bender, Amelie (Sensors and Actuators A: Physical)
With enhancing digitalization, condition monitoring is used in an increasing number of application fields across various industrial sectors. By its application, increased reliability as well as reduced risks and costs can be achieved. Based on different approaches, technical systems are monitored and measured data is analyzed to enable condition-based or predictive maintenance. To this end, machine learning approaches are usually implemented to diagnose the health states or predict the health index of the monitored system. However, these trained models are often black-box models, not intuitively explainable for a human. To overcome this shortcoming, a model-based approach based on physics is developed for piezoelectric bending actuators. Such a model enables a transparent representation of the system. Moreover, the model-based approach is extended by a parameter-estimation to account for sudden changes in behavior e. g. caused by occurring cracks.
Keywords: Condition Monitoring; Model-based approach Diagnostics; Varying conditions; Explainability; Piezoelectric bending actuators

Resilient Requirements Engineering - Gräßler, Iris; Oleff, Christian; Preuß, Daniel; Koch, Anna-Sophie (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Entwicklungsprojekte stehen in einem Spannungsfeld von Volatilität, Unsicherheit, Komplexität und Ambiguität (VUCA). Resilient Requirements Engineering (RRE) ist ein vielversprechender Ansatz, diesen Rahmenbedingungen gerecht zu werden und erfolgreich zu entwickeln. Es werden Methoden aus den drei Innovationsfeldern des RRE – Vorausschau, Effizienz und Nachhaltigkeit – angewendet, um Effizienzpotenziale in der Produktentwicklung zu nutzen und frühzeitig Nachhaltigkeitsdimensionen in der Ermittlung von Stakeholderbedürfnissen zu verankern.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

MAAS: Hiding Trojans in Approximate Circuits - Ahmed, Qazi Arbab; Awais, Muhammad; Platzner, Marco (The 24th International Symposium on Quality Electronic Design (ISQED'23), San Francisco, Califorina USA)

Minimum Edge Cuts in Overlay Networks - Schweichhart, Jonas

Unifying Gathering Protocols for Swarms of Mobile Robots - Castenow, Jannik; Harbig, Jonas; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Polymere unter Dehnung: Untersuchung der Filamententstehung von Polymerblends und deren Instabilitätsentstehung durch Partikeln - Temborius, Fiona; Neukötter, Moritz

Untersuchung dehnrheologischer Eigenschaften - Suspensionen auf Basis von Polymerlösungen - Almohammad, Ahmad; Neukötter, Moritz

Compact Metasurface-Based Optical Pulse-Shaping Device - Geromel, René; Georgi, Philip; Protte, Maximilian; Lei, Shiwei; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
Dispersion is present in every optical setup and is often an undesired effect, especially in nonlinear-optical experiments where ultrashort laser pulses are needed. Typically, bulky pulse compressors consisting of gratings or prisms are used to address this issue by precompensating the dispersion of the optical components. However, these devices are only able to compensate for a part of the dispersion (second-order dispersion). Here, we present a compact pulse-shaping device that uses plasmonic metasurfaces to apply an arbitrarily designed spectral phase delay allowing for a full dispersion control. Furthermore, with specific phase encodings, this device can be used to temporally reshape the incident laser pulses into more complex pulse forms such as a double pulse. We verify the performance of our device by using an SHG-FROG measurement setup together with a retrieval algorithm to extract the dispersion that our device applies to an incident laser pulse.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Hard carbon microspheres with bimodal size distribution and hierarchical porosity via hydrothermal carbonization of trehalose - Wortmann, Martin; Keil, Waldemar; Diestelhorst, Elise; Westphal, Michael; Haverkamp, René; Brockhagen, Bennet; Biedinger, Jan; Bondzio, Laila; Weinberger, Christian; Baier, Dominik; Tiemann, Michael; Hütten, Andreas; et al. (RSC Advances)
Hydrothermal carbonization (HTC) is an efficient thermochemical method for the conversion of organic feedstock to carbonaceous solids. HTC of different saccharides is known to produce microspheres (MS) with mostly Gaussian size distribution, which are utilized as functional materials in various applications, both as pristine MS and as a precursor for hard carbon MS. Although the average size of the MS can be influenced by adjusting the process parameters, there is no reliable mechanism to affect their size distribution. Our results demonstrate that HTC of trehalose, in contrast to other saccharides, results in a distinctly bimodal sphere diameter distribution consisting of small spheres with diameters of (2.1 ± 0.2) μm and of large spheres with diameters of (10.4 ± 2.6) μm. Remarkably, after pyrolytic post-carbonization at 1000 °C the MS develop a multimodal pore size distribution with abundant macropores > 100 nm, mesopores > 10 nm and micropores < 2 nm, which were examined by small-angle X-ray scattering and visualized by charge-compensated helium ion microscopy. The bimodal size distribution and hierarchical porosity provide an extraordinary set of properties and potential variables for the tailored synthesis of hierarchical porous carbons, making trehalose-derived hard carbon MS a highly promising material for applications in catalysis, filtration, and energy storage devices.
Keywords: General Chemical Engineering; General Chemistry

Theoretische Beschreibung des Polymerverhaltens in Polymerlösungen und - schmelzen: Simulationen anhand des Rolie-Poly-Modells - Bünder, Dirk; Neukötter, Moritz

Evaluation of self-built low-budget particle sensors (Study Project) - Al Mamoun, Mohamed; Neukötter, Moritz

Digital occupants – Wie digitale Medien die kommunikative Aushandlung von Freundschaften verändern - Teichert, Jeannine

Mediale Identitätsaushandlungen deutscher MigrantInnen im Zuge des Brexit - Teichert, Jeannine; Meister, Dorothee M. (MedienPädagogik)

"Lesungen vor Kindern sind für mich Theater" / Salah Naouras Sicht auf Wirkliches und Mögliches in Autor*innenlesungen für Kinder in der Schule - Kruse, Iris; Maubach, Bernd; Tönsing, Johanna (Salah Naoura)

Held*innenträume. Superheldinnen und Superhelden selbst erdacht / Paderborner Grundschulkinder werden auf die Begegnung mit Salah Naoura vorbereitet - Kruse, Iris; Schäfer, Luisa Maria (Salah Naoura)

Salah Naoura

Algorithms for the genome median under a restricted measure of rearrangement - Silva, Helmuth O.M.; Rubert, Diego P.; Araujo, Eloi; Steffen, Eckhard; Doerr, Daniel; Martinez, Fábio V. (RAIRO - Operations Research)
Ancestral reconstruction is a classic task in comparative genomics. Here, we study the genome median problem, a related computational problem which, given a set of three or more genomes, asks to find a new genome that minimizes the sum of pairwise distances between it and the given genomes. The distance stands for the amount of evolution observed at the genome level, for which we determine the minimum number of rearrangement operations necessary to transform one genome into the other. For almost all rearrangement operations the median problem is NP-hard, with the exception of the breakpoint median that can be constructed efficiently for multichromosomal circular and mixed genomes. In this work, we study the median problem under a restricted rearrangement measure called c4-distance, which is closely related to the breakpoint and the DCJ distance. We identify tight bounds and decomposers of the c4-median and develop algorithms for its construction, one exact ILP-based and three combinatorial heuristics. Subsequently, we perform experiments on simulated data sets. Our results suggest that the c4-distance is useful for the study the genome median problem, from theoretical and practical perspectives.
Keywords: Management Science and Operations Research; Computer Science Applications; Theoretical Computer Science

Sets of r-graphs that color all r-graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (arXiv:2305.08619)

Thermo‐chemo‐mechanical modelling of a curing process combined with mean‐field homogenization methods at large strains - Lenz, Peter; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Model-driven Collaborative Design of Professional Education Programmes With Extended Online Whiteboards - Wolters, Dennis; Engels, Gregor (MODELSWARD'23)

A Non-Linear Mean-Field Debonding Model at Large Strains for the Analysis of Fibre Kinking in Ud Composites - Cheng, Chun; Song, Chunlei; Mahnken, Rolf; Yuan, Zhipeng; Yu, Liang; Ju, Xiaozhe

A thermodynamic framework for the phase‐field approach considering carbide precipitation during phase transformations - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A finite strain gradient theory for viscoplasticity by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Ratings Meet Prices: The Dynamic Relationship of Quality Signals - Kaimann, Daniel; Spiess Bru, Clarissa Laura Maria; Frick, Bernd (Journal of Wine Economics)

Individualization of Public Transport – Integration of Technical and Social Dimensions of Sustainable Mobility - Ostermann, Moritz; Behm, Jonathan; Marten, Thorsten; Tröster, Thomas; Weyer, Johannes; Cepera, Kay; Adelt, Fabian (Towards the New Normal in Mobility)
In order to follow the 1.5 degree path of the Paris Climate Agreement, drastic greenhouse gas reduction measures are needed in the transport sector. The potential of public transport and new mobility services to reduce transport-related greenhouse gas emissions cannot yet be fully exploited, especially in rural regions. This paper presents the concept of an innovative mobility system, called NeMo.bil, that intends to fill the gap between individual and public transport to create a demand-oriented and sustainable mobility offer. The concept is based on convoy formation of autonomously driving lightweight vehicles serving the first and last mile and a larger towing vehicle carrying enough power and energy to move the convoy over longer distances at higher speeds. This combination of two different vehicles, intelligently controlled by a digital ecosystem, aims to significantly increasing energy, resource and cost efficiency. Based on an analysis of previous approaches for innovative mobility solutions, the concept is derived from a technical and sociological perspective and its potential for reducing energy demand is calculated.

Ultrafast Proton Transfer Pathways Mediated by Amphoteric Imidazole - Codescu, M.-A.; Kunze, T.; Weiß, M.; Brehm, Martin; Kornilov, O.; Sebastiani, D.; Nibbering, E. T. J. (J. Phys. Chem. Lett.)

A Force Field for Bio-Polymers in Ionic Liquids (BILFF) – Part 2: Cellulose in [EMIm][OAc] / Water Mixtures - Roos, E.; Sebastiani, D.; Brehm, Martin (Phys. Chem. Chem. Phys.)

Lactate-Based Ionic Liquids as Chiral Solvents for Cellulose - Radicke, J.; Roos, E.; Sebastiani, D.; Brehm, Martin; Kressler, J. (J. Polym. Sci.)

Definition of High-Risk Motion Patterns for Female ACL Injury Based on Football-Specific Field Data: A Wearable Sensors Plus Data Mining Approach - Di Paolo, Stefano; Nijmeijer, Eline M.; Bragonzoni, Laura; Gokeler, Alli; Benjaminse, Anne (Sensors)
The aim of the present study was to investigate if the presence of anterior cruciate ligament (ACL) injury risk factors depicted in the laboratory would reflect at-risk patterns in football-specific field data. Twenty-four female footballers (14.9 ± 0.9 year) performed unanticipated cutting maneuvers in a laboratory setting and on the football pitch during football-specific exercises (F-EX) and games (F-GAME). Knee joint moments were collected in the laboratory and grouped using hierarchical agglomerative clustering. The clusters were used to investigate the kinematics collected on field through wearable sensors. Three clusters emerged: Cluster 1 presented the lowest knee moments; Cluster 2 presented high knee extension but low knee abduction and rotation moments; Cluster 3 presented the highest knee abduction, extension, and external rotation moments. In F-EX, greater knee abduction angles were found in Cluster 2 and 3 compared to Cluster 1 (p = 0.007). Cluster 2 showed the lowest knee and hip flexion angles (p < 0.013). Cluster 3 showed the greatest hip external rotation angles (p = 0.006). In F-GAME, Cluster 3 presented the greatest knee external rotation and lowest knee flexion angles (p = 0.003). Clinically relevant differences towards ACL injury identified in the laboratory reflected at-risk patterns only in part when cutting on the field: in the field, low-risk players exhibited similar kinematic patterns as the high-risk players. Therefore, in-lab injury risk screening may lack ecological validity.
Keywords: Electrical and Electronic Engineering; Biochemistry; Instrumentation; Atomic and Molecular Physics; and Optics; Analytical Chemistry

Motor learning principles during rehabilitation after anterior cruciate ligament injury Prinzipien motorischen Lernens während der Rehabilitation nach vorderer Kreuzbandverletzung - Gokeler, Alli; Nijmeijer, E. M.; Heuvelmans, P.; Tak, I.; Ramponi, C.; Benjaminse, A. (Arthroskopie)
Keywords: Orthopedics and Sports Medicine